THE ROLE OF VIDEO CALLS AS FACILITATORS IN PAI STUDENT THESIS SESSIONS - Cahyono, Guntur; Marwanto, Marwanto; Hammam, Hammam (Nurul Jadid University, Paiton Probolinggo, East Java, 2022)
Video calls are the best way to be an easy facilitator in conducting thesis trials. The purpose of this study is to describe the role of video calls as a facilitator in a thesis trial. This research is a qualitative descriptive study. Technical data collection using interviews, documentation, and observation. Data were analyzed using reduction, presentation, and conclusion techniques. The subjects of this study were students of Islamic Religious Education (PAI). This research is located at the Faculty of Tarbiyah and Teacher Training IAIN Salatiga. The results of this study indicate that video calls provide a role as a facilitator in providing services and replace the role of offline thesis hearings. This research implies that during the pandemic, the thesis trial can still be done online using video calls so that the academic calendar can still run.